2012
DOI: 10.1128/jvi.00186-12
|View full text |Cite
|
Sign up to set email alerts
|

Glycoprotein G of Herpes Simplex Virus 2 as a Novel Vaccine Antigen for Immunity to Genital and Neurological Disease

Abstract: The envelope glycoproteins of herpes simplex virus 1 (HSV-1) and HSV-2, with the exception of glycoprotein G, elicit cross-reactive B-and T-cell responses. Human vaccine trials, using the cross-reactive glycoproteins B and D, have shown no protection against genital HSV-2 infection or disease. In this study, the mature form of glycoprotein G (mgG-2) of HSV-2 was used for immunization of mice, either alone or in combination with adjuvant CpG, followed by an intravaginal challenge with a lethal dose of a fully v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 55 publications
1
34
0
Order By: Relevance
“…It is generally accepted that an ideal HSV-2 vaccine should be capable of protecting individuals against new infection, sterilizing circulating viruses in infected individuals, and eliminating latent viral reservoirs (11,41,46). We demonstrated that HSV-2 gB-CCL19 fusion constructs were highly effective in inducing systematic immune responses, in particular a Th1-based Ab response, which was different from the immune profile induced by HSV-2 gB alone (44).…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…It is generally accepted that an ideal HSV-2 vaccine should be capable of protecting individuals against new infection, sterilizing circulating viruses in infected individuals, and eliminating latent viral reservoirs (11,41,46). We demonstrated that HSV-2 gB-CCL19 fusion constructs were highly effective in inducing systematic immune responses, in particular a Th1-based Ab response, which was different from the immune profile induced by HSV-2 gB alone (44).…”
Section: Discussionmentioning
confidence: 74%
“…It was well documented in animal models that an efficacious prophylactic HSV-2 vaccine will most likely induce a robust neutralizing-Ab response (11,41,46). Having demonstrated that fusion of CCL19 to gB at either end could significantly augment systemic and mucosal Ab responses to gB, we assessed the neutralizing activity of sera collected at days 14 and 49 postboost and at days 5, 9, and 11 postchallenge, as well as vaginal fluids tested at day 14 postboost.…”
Section: Gb-ccl19 Fusion Constructs Promote An Enhanced Virusneutralimentioning
confidence: 99%
See 1 more Smart Citation
“…The mixtures were then centrifuged at 20,000 ϫ g for 2 h (SW28.1 rotor) over the three-step discontinuous sucrose gradient consisting of 2 ml each of 50, 40, and 30% (wt/vol) sucrose in PBS, and 1-ml fractions were collected following side puncture of tube in the middle of the 50% sucrose layer. Each fraction was subjected to (i) titration of residual infectivity in the viral plaque assay, (ii) quantification of radioactivity in a scintillation counter, (iii) determination of the number of viral DNA copies based on quantitative PCR (qPCR) analysis (35), and (iv) determination of reactivity with mouse monoclonal antibodies against HSV glycoprotein B (gB) (clone B11D8; dilution, 1:100), gC (clone E5F7; dilution, 1:100), gE (clone B1E6; dilution, 1:100) and gG (clone O1C5; dilution, 1:100) and rabbit polyclonal antibody against the major capsid protein VP5 (NC1; dilution, 1:500) by an enzyme-linked immunosorbent assay (ELISA)-based method. The monoclonal antibodies were prepared and characterized in our laboratory (26,36,37), while polyclonal antibody NC1 was kindly provided by Gary Cohen and Roselyn Eisenberg (University of Pennsylvania).…”
Section: Methodsmentioning
confidence: 99%
“…Passive transfer of a panel of mouse monoclonal antibodies against HSV-2 glycoproteins with no HSV-2 neutralizing activity partially protected mice from HSV-2 footpad infection, and the effect correlated with ADCC activity of the monoclonal antibodies (49). An HSV-2 gG vaccine which induced low levels of serum neutralizing antibody but induced both ADCC and complement-mediated cytotoxicity partially protected mice from HSV-2 intravaginal challenge (50). More recently, vaccination of mice with a replication-defective HSV-2 gD deletion mutant protected animals from i.vag.…”
Section: Discussionmentioning
confidence: 99%